Travel Time Information Service Utilising Mobile Phone Tracking - Holm, Caj; Anžek, Mario; Kaštela, Slobodan (Promet - Traffic&Transportation, 2004)
This paper discusses the suitability of mobile phone positioningdata for travel time information. The Finnish NationalRoad Administration Finnra has carried out a study on thesubject (1) and managed pilot installations on two road sections(6) in order to determine the feasibility of mobile phonetracking for traffic monitoring and management purposes. Accordingto the study and the pilots, the mobile phone positioningcan provide useful link monitoring data, i. e. the travel timeand speed. Mobile phone tracking was found to be a very promisingtool for implementing travel time information service todrivers.